ANALISIS PENGARUH EKSPOR, INVESTASI ASING LANGSUNG DAN INVESTASI PORTOFOLIO TERHADAP NILAI TUKAR RUPIAH DI INDONESIA TAHUN 2006-2017 - Rikki Manurung; Rahmat Richard; Mardiana Mardiana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research aims to knowing how much the effect of exports of foreign direct investment and portfolio investment to the rupiah exchange rate in Indonesia in 2006-2017. The data used in this study is the data time seris obtained from the Central Bureau of Statistics and Bank Indonesia. This research uses quantitative research methods, and analyzed using multiple linear regression analysis tools using SPSS 20 for windows computer application. In this study the independent variables are export (X1), foreign direct investment (X2) and portfolio investment (X3) and the dependent variable is the exchange rate of rupiah (Y). From the result of the research, it is found that the export variable of foreign direct investment and portfolio investment simultaneously give significant influence to the rupiah exchange rate. From the partial / individual test, it is found that foreign direct investment variable gives bigger contribution compared to export variable and portfolio investment to rupiah exchange rate.Keywords : Export, Foreign Direct Investment, Portfolio Investment, Rupiah Exchange Rate